The co-benefits of a low-carbon future for PM2.5 and O3 air pollution in Europe - C. J. Clayton; D. R. Marsh; S. T. Turnock; S. T. Turnock; A. M. Graham; K. J. Pringle; C. L. Reddington; R. Kumar; J. B. McQuaid (Atmospheric Chemistry and Physics)
There is considerable academic interest in the potential for air quality improvement as a co-benefit of climate change mitigation. Few studies use regional air quality models for simulating future co-benefits, but many use global chemistry–climate model output. Using regional atmospheric chemistry could provide a better representation of air quality changes than global chemistry–climate models, especially by improving the representation of elevated urban concentrations. We use a detailed regional atmospheric-chemistry model (WRF-Chem v4.2) to model European air quality in 2050 compared to 2014 following three climate change mitigation scenarios. We represent different climate futures by using air pollutant emissions and chemical boundary conditions (from CESM2-WACCM output) for three shared socioeconomic pathways (SSP1-2.6, SSP2-4.5 and SSP3-7.0: high-, medium- and low-mitigation pathways respectively).